2019
DOI: 10.1007/s40520-019-01276-6
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic resections in elderly patients with high American Society of Anesthesiologists’ risk score: a view from a tertiary care center

Abstract: Background More than 60% of patients affected by pancreatic cancer are ≥ 65 years of age. Surgery represents the only potentially curative treatment for malignant pancreatic neoplasia and a useful treatment for benign diseases. Aim To evaluate outcomes in elderly patients with ASA risk score 4 who underwent pancreatic resection compared to younger patients and elderly patients with lower anesthesiological risk. Methods A consecutive series of 345 patients underwent pancreatic resection between 2010 and 2017 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Age is not considered as an assessment measure in the ASA grading system, 8 and an older age can potentially increase the perioperative risk in patients with poor physical status. 22,23 In this study, roughly 50% of these patients were elderly. Similar to the results in the total cohort, elderly patients with ASA III-IV experienced a significantly higher incidence of medical complications compared to the elderly with ASA I-II.…”
Section: Discussionmentioning
confidence: 66%
“…Age is not considered as an assessment measure in the ASA grading system, 8 and an older age can potentially increase the perioperative risk in patients with poor physical status. 22,23 In this study, roughly 50% of these patients were elderly. Similar to the results in the total cohort, elderly patients with ASA III-IV experienced a significantly higher incidence of medical complications compared to the elderly with ASA I-II.…”
Section: Discussionmentioning
confidence: 66%
“…Selecting the most reasonable treatment for the aged is especially difficult among patients with suspected pancreatic cancer and potentially poor prognoses or with suspected premalignant pancreatic lesions with a potentially uncompromised life expectancy. Pancreatic resections are high-risk surgery, and in earlier studies, [1][2][3][4] preoperative frailty, age, chronic kidney disease, high American Society of Anesthesiologists (ASA) class, and sarcopenia have been associated with postoperative morbidity. However, it has been reported that neither short-term 5,6 nor long-term prognoses among the aged necessarily differ from those of unselected, younger patient cohorts.…”
Section: Introductionmentioning
confidence: 99%